Language Anxiety and Attitude of Secondary School Students towards Learning English - Muhammad Athar Hussain (PJE, 2023)
In countries where English is taught as a foreign language, learners suffer various levels of being anxious and develop a specific attitude towards English. The paper examined foreign language anxiety of 10th grade students and their attitude towards foreign language learning. Sample of the study was 360 male and 360 female students of 10th grade students of public sector secondary schools from six districts of the Punjab Province of Pakistan. Foreign Language Classroom Anxiety (FLCAS) scale was used to investigate anxiety of the students and attitude towards English was found by using English language attitude scale. The data were analyzed quantitatively using SPSS. t-test was used to find out gender differences for language anxiety and attitude. Relationship of anxiety with attitude of the students was determined though Pearson product moment coefficient. Results revealed that significant differences existed between male and female students for foreign language anxiety and attitude towards foreign language learning. Results also indicated that significant negative correlation was found between foreign language anxiety and students’ attitude towards foreign language learning. Girls showed less anxiety in English language class and had more positive attitude towards English. It was suggested that training might be given to English language teachers on modern pedagogical patterns. English language Curriculum might be redesigned keeping the context of the learners in mind.